Effects of genotype and salting time on chemical, physical and sensorial traits of a new pig seasoned meat product 'Cuore Di Spalla'. Issue 1 (2nd January 2019) - Sirtori, Francesco; Bozzi, Riccardo; Franci, Oreste; Calamai, Luca; Crovetti, Alessandro; Bonelli, Antonio; Benvenuti, Doria; Aquilani, Chiara; Pugliese, Carolina
Abstract: The aim of this work was to determine the chemical, physical and sensorial characteristics of a cured product called 'Cuore di Spalla', resulting from two different pig genotypes (G) and two salting times (S). Fourteen Duroc × Large White (D × LW) and 14 Cinta Senese × Large White (CS × LW), reared in the same condition in outdoor and fed commercial mixture. The animals were slaughtered at 10 months of age which corresponds to an average live weight of 143 ± 15 kg for D × LW and 122 ± 15 kg for CS × LW. The right shoulders were salted for 3 days (L) and the left ones for 5 days (H). Physical (colour, texture profile analysis), chemical (moisture; crude protein; IMF; ash; salt; total lipids; fatty acids) and sensorial analyses (by panellists' group) as well as volatile compounds profile (by SPME-GC-MS technique) were determined at the end of seasoning period. The genotype affected product's size (1484.3 vs 1857.1 g of final weight for CS × LW and D × LW respectively), chemical characteristics and texture (cohesiveness 0.50 vs 0.53 and springiness 6.73 vs 7.12 for CS × LW and D × LW respectively). Aromatic profile was less affected by the factors considered or at least the panellists were not able to discriminate the effect. The main family of volatile compounds affected by genotype was alcohols. Salting time seemed to affect only the parameters closely related to salt (16.52 vs 15.33% of salt and 5.15 vs 4.35 for saltiness in H vs L respectively). Highlights: The genotypes determined differences in size, fat quantity and physical-chemical parameters of the 'Cuore di Spalla' product. Very limited differences in the aromatic profile were found. Both salting times led to high salt content in the product. It seems feasible to produce the 'Cuore di Spalla' with further reduction of salting times.